URGENSI PENGATURAN KEWENANGAN DESA ADAT DALAM MENUNJANG ERA NEW NORMAL KEPARIWISATAAN BUDAYA BALI - Satrya Wibawa, Gede Yoga (VYAVAHARA DUTA, 2020)
Bali, which is an international tourist destination, makes tourism as a major commodity so that the impact of the Covid 19 pandemic is enormously felt for the Bali economy and tourism actors involved. For instance, almost about 98% of tourist attractions, hotels, restaurants, spas and tourism facilities are closed to the public. With the intention that it brings a very harsh recession to the economy of the Balinese people themselves, involving the indigenous village in handling the Covid-19 outbreak in Bali is very appropriate. By involving the indigenous communities, in this case the indigenous village, it will directly touches up to the littlest area in Bali, the Banjar environment. With a more massive structure, it is also hoped that it can effectively break the chain of the spread of Covid 19 in Bali province. This writing uses the normative legal research method. The study of legislation and literature is used to formulate the authority of indigenous villages in the new era of Balinese culture tourism which will be faced after the Covid-19 pandemic. Finally, it can be concluded that the position of the indigenous villages in assisting the higher tasks of the government is legally very strong, from the constitution to the legislation below recognizing the existence and role of the indigenous villages. On this basis, it is appropriate for the indigenous village to be given its own portion as an integral part of the structure both legally and administratively. Secondly, the authority of indigenous villages in carrying out their functions in the Covid Task Force for the prevention of Covid 19 in Bali province has been very clear and this can be the basis for further enhancing role of indigenous villages in the new era of cultural tourism in Bali which will be rebuilt after this pandemic. Finally, the optimization of the role of indigenous villages in the acceleration of Covid 19 prevention in Bali has been able to run well and can answer all doubts from various parties who during the pandemic might underestimate the magnificent role of this indigenous village, thus the Provincial Government of Bali should be able to consider an alternative management of indigenous village-based tourism going forward.Keywords: Covid-19, Indigenous Village, Bali Cultural Tourism, New Normal